2020
DOI: 10.4103/ijd.ijd_485_20
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of venous clinical severity score and venous disability score with dermatology life quality index in chronic venous insufficiency

Abstract: Background: Chronic venous insufficiency (CVI) is an underestimated public health problem involving the lower limbs. It exerts a significant impact on patient's quality of life (QoL). The severity of the disease was measured by venous clinical severity score (VCSS) and venous disability score (VDS). Aims: The aim of the study was to evaluate VCSS, VDS, and dermatology life quality index (DLQI) among the patients of CVI and to evaluate the correlation among DLQI with VCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…In this study, the proportion of males was higher than females (6.1:1). A study done by Mallick et al [ 15 ] in 2020 showed VCSS positively correlating with DLQI and CVI exerting small to moderate effect on patient’s QoL, whereas in our study it showed moderate to very large effect. In a study done by Gillet et al [ 21 ] on 60 patients, it was found that increased VCSS values directly correlate with increased CEAP scores.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In this study, the proportion of males was higher than females (6.1:1). A study done by Mallick et al [ 15 ] in 2020 showed VCSS positively correlating with DLQI and CVI exerting small to moderate effect on patient’s QoL, whereas in our study it showed moderate to very large effect. In a study done by Gillet et al [ 21 ] on 60 patients, it was found that increased VCSS values directly correlate with increased CEAP scores.…”
Section: Discussioncontrasting
confidence: 79%
“…The CEAP classification was developed by an international consensus conference for the notification of diagnostic details in chronic venous disease, as well as for routine patient documentation and treatment [3,[13][14]. DLQI is the first dermatology-specific quality of life questionnaire published to measure dermatological distress [15][16][17][18][19]. In the Edinburg vein study, the prevalence of CVI is 9.4% in men and 6.6% in women [20].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of non-adherence to treatment recommendations include chronicity of VLUs, increased recurrence rate ( Finlayson et al, 2018 ), infection ( Bui et al, 2019 ) and secondary squamous cell carcinoma ( Reich-Schupke et al, 2015 ). Disease progression ( Meulendijks et al, 2020 ) and associated complications exacerbate wound pain ( Leren et al, 2020 ), increase wound exudate, and reduce patients’ mobility, which in turn contributes to disease progression ( Meulendijks et al, 2019 ), leads to premature disability ( Mallick et al, 2020 ), and inadvertently influences patients’ quality of life ( Barnsbee et al, 2019 ). Management of these complications require complex interventions and highlights the need for optimal care for this underestimated condition.…”
Section: Introductionmentioning
confidence: 99%
“…Originally proposed by Rutherford, the VCSS is currently the most commonly used scoring system, which can be objective and truly reflect the severity of chronic venous disease in patients, and its evaluation involves 10 aspects, including pain, oedema, ulcer extent, and inflammatory response 20 . Liu pointed out that ultrasound‐guided endoluminal radiofrequency ablation combined with lauromacrogol is effective in the treatment of VVLE, reducing pain in patients, and can reduce the VCSS 21 .…”
Section: Discussionmentioning
confidence: 99%
“…19 Originally proposed by Rutherford, the VCSS is currently the most commonly used scoring system, which can be objective and truly reflect the severity of chronic venous disease in patients, and its evaluation involves 10 aspects, including pain, oedema, ulcer extent, and inflammatory response. 20 Liu pointed out that ultrasound-guided endoluminal radiofrequency ablation combined with lauromacrogol is effective in the treatment of VVLE, reducing pain in patients, and can reduce the VCSS. 21 The results of this study showed that acoustic-guided foam sclerotherapy combined with endovascular radiofrequency ablation was superior to surgical treatment for the improvement of VCSS score, with more significant therapeutic effect, which could effectively relieve the condition of patients with VVLE.…”
Section: Discussionmentioning
confidence: 99%